Golden Needle Mushroom: A Culinary Medicine with Evidenced-Based Biological Activities and Health Promoting Properties - Tang, Calyn; Hoo, Pearl Ching-Xin; Tan, Loh Teng-Hern; Pusparajah, Priyia; Khan, Tahir Mehmood; Lee, Learn-Han; Goh, Bey-Hing; Chan, Kok-Gan (Frontiers in Pharmacology, 2016)
Flammulina velutipes (enoki, velvet shank, golden needle mushroom or winter mushroom), one of the main edible mushrooms on the market, has long been recognized for its nutritional value and delicious taste. In recent decades, research has expanded beyond detailing its nutritional composition and delved into the biological activities and potential health benefits of its constituents. Many bioactive constituents from a range of families have been isolated from different parts of the mushroom, including carbohydrates, protein, lipids, glycoproteins, phenols, and sesquiterpenes. These compounds have been demonstrated to exhibit various biological activities, such as antitumour and anticancer activities, anti-atherosclerotic and thrombosis inhibition activity, antihypertensive and cholesterol lowering effects, anti-aging and antioxidant properties, ability to aid with restoring memory and overcoming learning deficits, anti-inflammatory, immunomodulatory, anti-bacterial, ribosome inactivation and melanosis inhibition. This review aims to consolidate the information concerning the phytochemistry and biological activities of various compounds isolated from F. velutipes to demonstrate that this mushroom is not only a great source of nutrients but also possesses tremendous potential in pharmaceutical drug development.